Effect of the addition of phosphotungstic acid on the thermal stability of zirconium oxide (2014)
Zirconium hydroxide [Zr(OH)4] was synthesized by the sol-gel method using zirconium n-butoxide and 1-butanol as synthesis precursors. A part of the synthesized material was impregnated with phosphotungstic acid (H3PW12O40) in order to evaluate the effect of this dopant agent on the thermal, textural and structural properties of zirconium oxide (ZrO2). Pure and modified hydroxides were calcined in an air flow at 400, 500 and 600°C for 3 h and afterwards were characterized by thermal analysis, infrared spectroscopy, X-ray diffraction and nitrogen physisorption. Results showed that the interaction between the heteropolyanion and zirconium oxide surface produces a stabilizing effect of the crystalline structure and delays the drastic sintering of the material caused by the thermal treatment, obtaining high specific surface areas and small crystallite size for the modified zirconium oxides.